Medical students' perception on euthanasia, orthothanasia and dysthanasia (Research, Society and Development, 2021)
Objectives: To assess the knowledge level on euthanasia, orthothanasia and dysthanasia among medical students at universities in Aracaju; to analyze whether knowledge on euthanasia, dysthanasia and orthothanasia has been improved over the years in medical courses and to verify whether medical students agree/disagree with the practices of euthanasia, orthothanasia and dysthanasia. Methodology: Exploratory, descriptive, cross-sectional and quantitative study; produced through a questionnaire applied to medical students at two universities in Aracaju. Data analyzed with descriptive statistics and significance level set at p